ANALISIS CITRA FOTO UDARA UNTUK IDENTIFIKASI SALINITAS PERMUKAAN TAMBAK AIR PAYAU - Romansah Wumu; Shabri Indra Suryalfihra (Jurnal Sains Informasi Geografi (J SIG), 2022)
East Kalimantan Province is sufficiently potential for brackish water pond with an area of 113,053.1 ha (gross land area) and 82,714 ha (clean land area). This potential needs to be maximized by paying attention to land suitability for ponds. One of the parameters of land suitability for ponds is water salinity. Water salinity can be measured directly by taking water samples in the field; however, this method is less effective considering that water is dynamic so that the measurement results of water salinity often change over time. Remote sensing technology facilitates the observation of objects on the earth's surface without having to directly touch the object. Several studies using satellite imagery have proven to be able to measure salinity of water surface using a special algorithm. The findings of the research discover that the algorithm is developed using the visible light band (RGB). This allows the results of aerial photos using drones to be used to measure the salinity of brackish water pond by using an algorithm. Based on this explanation, this research aims at applying radiometric corrections from aerial photographs using drones and then creating a pond salinity algorithm using drone aerial photographs. The algorithm is obtained by finding the best correlation linearly or order 2 polynomial from pond water salinity data with reflectance values and Digital Number (DN) aerial photos. It is found that the results obtained by the algorithm with the best performance is the second polynomial algorithm for blue band reflectance data with an R2 value of 0.896 and an RMSE of 0.744. The salinity of pond water ranges from 0 – 9.65 ppt.